Socio-Economic Reintegration of Former Migrant Workers in Indonesia: Sustainable Livelihoods and Socio-Cultural Models - Pratama, Inka Nusamuda; Hadi, Ayatullah; Sutarna, Iwan Tanjung (Jurnal Pemerintahan dan Politik Lokal, 2025)
This study aims to develop a socio-economic reintegration model for returnee migrant workers in Indonesia based on the Sustainable Livelihood framework and socio-cultural approaches. Although numerous studies have highlighted the importance of these two approaches separately, their integration within the context of migrant reintegration in Indonesia remains limited. Employing a qualitative method through a Systematic Literature Review (SLR), this research identifies, evaluates, and synthesizes relevant studies published over the past six years (2019–2025) using the Dimensions and Scopus databases. The findings reveal that reintegration is a complex process influenced by structural, socio-cultural, as well as local and global dynamics. Social capital and adaptive capacity emerge as key elements in addressing reintegration challenges, particularly during crises such as the COVID-19 pandemic. Therefore, an effective reintegration model must be holistic, community-based, and supported by cross-sector collaboration and institutional transformation. This study contributes both conceptually and practically to the design of inclusive and adaptive reintegration policies that are responsive to the dynamics of global labor mobility.